Small and Medium Enterprises Brand Positioning Through Guerilla Marketing Principles - Lubytė, Viltė (Vilnius University Open Series, 2021)
The article analyses the positioning process of small and medium enterprises using the principles of guerrilla marketing. At the beginning of a business start-up, the positioning process becomes crucial to gain a competitive advantage in a crowded market. The problem is that small business cannot compete in the market with the same marketing tools as large companies. Exceptionally, small businesses often face three problems: lack of financial resources for advertising, lack of marketing specialists, inability to compete with large companies. The scientific literature analysis allowed us to systematise the essential principles of memorising the brand’s position using guerrilla marketing principles. The model of small and medium business brand positioning through guerrilla marketing and its principles are also presented. Guerrilla marketing is a particularly suitable way for small businesses as it requires creativity, intellectual and time investment rather than financial resources.